PENGARUH PEMBERIAN PUPUK KASCING DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Vigna radiata L.) - Handayani, Fitri; Murniati, Murniati; Yulia, Arnis En (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of vermicompost fertilizer and NPK fertilizers, as well as get a perfect dose of NPK and vermicompost fertilizer for the growth and production of green peas. This research has been conducted inexperimental garden Technical Implementation Unit (UPT) Faculty of Agriculture, University of Riau. This study was conducted over three (3) months from April to July 2017. This study was conducted in 3x3 factorial experiments were prepared using Completely Randomized Design (CRD), the first factor vermicompost fertilizer dose (K) consisting of 3 levels: 5, 10 and 15 ton/ha. Factor II dose of NPK fertilizer (P), which consists of three levels :100, 200and 300 kg/ha. From the two factors obtained 9 treatment combinations, each combination treatment was repeated 3 times, so it can conclude that 27 units each experimental trial consisted of 50 plants and 10 plants of which are used as a sample. Parameters measured were plant height, number of productive branches, flowering age, harvesting age, number of pods crop, the percentage of peas pithy, production per m2, weight of 100 seeds. Data were analyzed statistically using analysis of variance followed by Duncan's multiple range test at 5% level. Vermicompost and NPK fertilizer interaction real effect on plant height and effect no significant effect on other parameters. The combination of vermicompost fertilizer 15 ton/ha and NPK 200 kg/ha is the best treatment with the result per m2121.92 g (1.21 ton/ha). The planting of green peas Vima 1 variety it would be best to use vermicompost fertilizer15 ton/ha and NPK fertilizer 200 kg/ha. Keywords: green peas, vermicompost fertilizer and NPK